The distribution pattern of segmental vitiligo: clues for somatic mosaicism. (13th December 2012) - van Geel, N.; Speeckaert, R.; Melsens, E.; Toelle, S.P.; Speeckaert, M.; De Schepper, S.; Lambert, J.; Brochez, L.
Summary Background Segmental vitiligo is characterized by a unilateral and localized distribution. So far, the underlying mechanism is still an enigma. Objectives To get an insight into the aetiopathogenesis of segmental vitiligo by comparison with the distribution pattern of dermatoses with a possible mosaic or neurogenic background. Methods In this retrospective observational study the distribution pattern of 724 unilateral, linear or band‐shaped control lesions was compared with 181 segmental vitiligo lesions. Clinical photographs were used to score similarities according to a defined grading system (scale ranging from 0 for no similarities to 4 for complete similarity). Control lesions were evaluated both individually and after grouping into different cell types. Results In general, only a minority of cases (36·9%), showed similarities (grade 1–4) between control lesions and segmental vitiligo. Grade 2–4 similarities were seen mainly in segmental lentiginosis (73·7%, P < 0·001). The best grade for correspondence (grade 3–4) was observed significantly more only in segmental lentiginosis (36·8% vs. 3·5%, P < 0·001) and epidermal naevus verrucosus (12·5% vs. 3·7%, P = 0·008) compared with the other control lesions. The distribution pattern of segmental vitiligo significantly overlapped those of other disorders originating from melanocytes. Conclusions Our results demonstrate that the distribution pattern of segmental vitiligo is not entirely similar to any other skin disease, although some mosaic skin disorders have more overlap with segmental vitiligo than others. The remarkable clinical similarity with several cases of mosaic diseases involving melanocytes supports the hypothesis that cutaneous mosaicism may be involved in segmental vitiligo.